Manajemen Strategi Pemberdayaan Alumni Di SMKN 1 Praya Kabupaten Lombok Tengah - Dzakir, Rahmat (Jurnal Ilmiah Mandala Education (JIME), 2022)
Strategic management has a significant role in empowering SMK (Vocational High School) alumni. Thus, this study aimed to 1) determine the principal's role in planning alumni empowerment strategies; 2) unveil the principal's role in implementing the alumni empowerment strategy. Finally, 3) discover the principal's role in evaluating strategies for empowering alumni of SMKN 1 Praya, Central Lombok district. Therefore, this qualitative research was carried out at SMKN 1 Praya, Central Lombok Regency. Moreover, data was collected through observation, in-depth interviews, and documentation. The data were then analyzed using the Milles & Huberman technique, including data reduction, data presentation, and conclusion drawing. In addition, credibility, transferability, dependency, and certainty are utilized to examine the data validity. Hence, the findings indicated that: 1) Planning of alumni empowerment strategies at SMKN 1 Praya includes adjusting the vision and mission with orientation to the absorption of alumni in local and global DUDI, planning for the formation of BKK, BPBK, Tracer study 2) Implementation of alumni empowerment strategy management includes the establishment of special job fairs (BKK), BPBK, Tracer study, MoU with DUDI. 3) Management evaluation Alumni empowerment strategies include preparing written and oral reports.